ПРО НЕОДНОРІДНІСТЬ НАМАГНІЧУВАННЯ ЦИЛІНДРИЧНИХ ОСЕРДЬ В ОДНОРІДНОМУ МАГНІТНОМУ ПОЛІ - Чуніхін, К.В. (Інститут електродинаміки НАН України, Київ, 2019)
The inhomogeneity of the magnetization of cylindrical cores of an electromagnet in a constant uniform external magnetic field is studied taking into account the nonlinearity of the magnetic properties of the material. The iterative algorithm for calculating resulting magnetic field inside a core, based on the numerical solution of the integral equation for the surface density of fictitious magnetic charges in conjunction with the approximated magnetization curve of a material, is proposed. The convergence of the iterative algorithm for arbitrary initial values of magnetic permeabilities is established. References 9, table 1, figures 3.